Two‐stage composite megathrust rupture of the 2015 Mw8.4 Illapel, Chile, earthquake identified by spectral‐element inversion of teleseismic waves - Shiann‐Jong Lee; Te‐Yang Yeh; Tzu‐Chi Lin; Yen‐Yu Lin; Teh‐Ru Alex Song; Bor‐Shouh Huang (Geophysical Research Letters)
Abstract The Mw8.4 Illapel earthquake occurred on 16 September was the largest global event in 2015. This earthquake was not unexpected because the hypocenter was located in a seismic gap of the Peru‐Chile subduction zone. However, the source model derived from 3‐D spectral‐element inversion of teleseismic waves reveals a distinct two‐stage rupture process with completely different slip characteristics as a composite megathrust event. The two stages were temporally separated. Rupture in the first stage, with a moment magnitude of Mw8.32, built up energetically from the deeper locked zone and propagated in the updip direction toward the trench. Subsequently, the rupture of the second stage, with a magnitude of Mw8.08, mainly occurred in the shallow subduction zone with atypical repeating slip behavior. The unique spatial‐temporal rupture evolution presented in this source model is key to further in‐depth studies of earthquake physics and source dynamics in subduction systems.